2016
DOI: 10.1542/peds.2016-2013
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Invasive Early-Onset Neonatal Sepsis, 2005 to 2014

Abstract: GBS prevention efforts have not led to an increasing burden of early-onset E coli infections. However, the stable burden of E coli sepsis and associated mortality underscore the need for interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
324
4
22

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(373 citation statements)
references
References 17 publications
23
324
4
22
Order By: Relevance
“…Despite the advances in neonatal medicine, EOS remains a potentially fatal condition that affects approximately 0.3–0.8/1,000 infants born at ≥35 weeks’ gestation in high-resource settings [1, 2]. Current neonatal sepsis management algorithms provide neither a satisfactory framework for consistent and objective risk assessment nor an estimate of patient-specific risks.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the advances in neonatal medicine, EOS remains a potentially fatal condition that affects approximately 0.3–0.8/1,000 infants born at ≥35 weeks’ gestation in high-resource settings [1, 2]. Current neonatal sepsis management algorithms provide neither a satisfactory framework for consistent and objective risk assessment nor an estimate of patient-specific risks.…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis and septic shock are recognized as one of the most frequent causes of mortal complications in neonatal intensive care units worldwide. It has been observed that early-onset sepsis has become a serious and common issue among neonates, especially preterm infants [2]. Neonatal period is the most critical stage in the life of newborn babies, and neonatal sepsis is one of the most common causes for mortality at this age.…”
Section: Introductionmentioning
confidence: 99%
“…La vigilancia activa de las infecciones invasoras indica que la prevalencia de E. coli ha aumentado en los últimos años, como asimismo la frecuencia de resistencia a ampicilina (19). Esto último podría relacionarse con el cambio en las prácticas de la profilaxis intraparto para evitar infecciones invasoras tempranas por SGB (7,19).…”
Section: Discussionunclassified
“…Las más frecuentes son causadas por Streptococcus agalactiae o Streptococcus del grupo B (SGB) y por Escherichia coli (7,8). Corresponde al obstetra la prevención del parto prematuro y de los resultados adversos perinatales en estos casos (9,10).…”
Section: Introductionunclassified